Penerapan Pendekatan Whole Language dalam Pengembangan Kemampuan Berbahasa Indonesia Siswa Sekolah Dasar - I Ketut Suparya (Universitas Sarjanawiyata Tamansiswa, 2021)
This study describes the nature of learning Indonesian and to describe the application of the whole language approach in learning Indonesian in elementary schools. The method used in this research is a qualitative research method. This research was conducted at the Elementary School 4 Dharmasaba. The data analysis technique used is Miles and Huberman's qualitative data analysis technique, which comprises reducing data, presenting data and drawing conclusions and verifying. Based on the results of interviews and document analysis conducted in the research process, it can be concluded that: (1) Indonesian language learning at the elementary school level includes listening, speaking, reading and writing skills and has been adapted on the demands of the 2013 curriculum. (2) Application of the whole approach language in Indonesian language learning has improved students' Indonesian learning outcomes, as evidenced by the increase in the average learning outcomes before and after the application of the whole language approach from 76.75 to 80.25.